Where are all the Girls and Indigenous People at IGSA@ND?. Issue 2 (1st June 2021) - ,; Moccasin, Cindy; McNab, Jessica; Vanner, Catherine; Flicker, Sarah; Altenberg, Jennifer; Wuttunee, Kari-Dawn
Abstract: We adopt an autoethnographic approach to share critical reflections from the Young Indigenous Women's Utopia girls' group about our experiences attending the 2019 International Girlhood Studies Association conference at the University of Notre Dame (IGSA@ND). Moments of inspiration included sharing our work and connecting with local Indigenous youth. Challenging moments included feeling isolated and excluded since the only girls present at the conference were Indigenous people in colonial spaces. We conclude with reflection questions and recommendations to help future conference organizers and participants think through the politics and possibilities of meaningful expanded stakeholder inclusion at academic meetings.